Coping strategies following the diagnosis of a fetal anomaly: A scoping review - Tingting Zhang; Tingting Zhang; Wei-Ti Chen; Qingnan He; Ying Li; Huiting Peng; Jiaying Xie; Hengfen Hu; Chunxiang Qin; Chunxiang Qin (Frontiers Media S.A., 2023)
IntroductionMany women experience severe emotional distress (such as grief, depression, and anxiety) following a diagnosis of fetal anomaly. The ability to cope with stressful events and regulate emotions across diverse situations may play a primary role in psychological wellbeing. This study aims to present coping strategies after disclosing a fetal anomaly to pregnant women.MethodsThis is a scoping review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews (PRISMA-ScR). Electronic databases, including Web of Science (WOS, BCI, KJD, MEDLINE, RSCI, SCIELO), CINAHL, and EBSCO PsycARTICLES, were used to search for primary studies from the inception of each database to 2021. The keywords were determined by existing literature and included: "fetal anomaly," "fetal abnormality," "fetal anomaly," "fetal abnormality" AND "cope," "coping," "deal," "manage," "adapt*," "emotion* regulate*," with the use of Boolean operators AND/OR. A total of 16 articles were reviewed, followed by advancing scoping review methodology of Arksey and O'Malley's framework.ResultsIn this review, we identified 52 coping strategies using five questionnaires in seven quantitative studies and one mixed-method study. The relationship between coping strategies and mental distress was explored. However, the results were inconsistent and incomparable. We synthesized four coping categories from qualitative studies and presented them in an intersection.ConclusionThis scoping review identified the coping strategies of women with a diagnosis of a fetal anomaly during pregnancy. The relationship between coping strategies and mental distress was uncertain and needs more exploration. We considered an appropriate measurement should be necessary for the research of coping in women diagnosed with fetal anomaly pregnancy.